2017
DOI: 10.3390/en10070853
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Available Tools for Dynamic Mooring Analysis of Wave Energy Converters

Abstract: The focus on alternative energy sources has increased significantly throughout the last few decades, leading to a considerable development in the wave energy sector. In spite of this, the sector cannot yet be considered commercialized, and many challenges still exist, in which mooring of floating wave energy converters is included. Different methods for assessment and design of mooring systems have been described by now, covering simple quasi-static analysis and more advanced and sophisticated dynamic analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Damage conditions, such as line breakage, may also be included. The degree of accuracy that linear-potential-flow-based models can reach when used to simulate extreme waves is a subject of recent studies ( [13,22,31]), and it is clearly expected to be larger in deep-water, where non-linearities are less important.…”
Section: Short Description Of the Numerical Modelmentioning
confidence: 99%
“…Damage conditions, such as line breakage, may also be included. The degree of accuracy that linear-potential-flow-based models can reach when used to simulate extreme waves is a subject of recent studies ( [13,22,31]), and it is clearly expected to be larger in deep-water, where non-linearities are less important.…”
Section: Short Description Of the Numerical Modelmentioning
confidence: 99%
“…In case of floating bodies with a complex shape, the Boundary Element Method (BEM) is commonly implemented [17,18], obtaining steady solutions by solving numerically a boundary value problem in the frequency-domain. However, although these frequency-domain models are powerful and accurate in solving linear problems, they are usually implemented to provide hydrodynamic characteristics of floating devices and are coupled to time-domain simulations to analyze the response of moored structures [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, a number of cable models have been explored, validated or coupled with the multi-body dynamics of floating offshore wind turbines and wave energy devices for numerical simulation, including the finite element model [8,9], the multi-body dynamics model [10], the lumped mass models [11,12] and the finite difference model [13][14][15][16][17]. A review of the available models and simulation tools of mooring cables can be found in [18,19]. Presently, mathematical modeling of mooring cables is still a topic area, e.g.…”
Section: Introductionmentioning
confidence: 99%